Conditional synergy: Impact of nutrient abundance on multispecies biofilm formation and sanitizer tolerance - Pant K; Palmer J; Flint S (Elsevier Ltd, 2026)
Bacteria exist in varying nutrient conditions and complex microbial consortia. Pseudomonas fluorescens, Staphylococcus aureus, and Listeria monocytogenes are commonly occurring biofilm-formers, share a similar nutritional niche, and have been isolated from common surfaces in multispecies environments. Biofilm properties, including biomass (O.D590 nm), cell concentration (log CFU/cm2), exopolysaccharide content (μg/cm2), structure, and sanitizer tolerance (sodium hypochlorite), were observed under varying nutrient (full-strength TSB and 10 % TSB) conditions on polystyrene surfaces for single and multispecies biofilm. The synergistic interactions between the bacteria in multispecies biofilm were found to be nutrient-dependent, with significantly higher (p < 0.05) biofilm formation, exopolysaccharide content, and sanitizer tolerance in high nutrient conditions (TSB) compared with low nutrient conditions (10 % TSB). The cell concentrations in the biofilm (single and multispecies) were found to be comparable between TSB and 10 % TSB. All three bacteria involved showed increased tolerance against sanitizers in the multispecies arrangement compared to their single-species counterparts, with significantly higher survival for L. monocytogenes (5.3 log CFU/cm2) in a multispecies biofilm compared to its single-species counterpart (2.3 log CFU/cm2). A positive correlation was observed between exopolysaccharide concentration and sanitizer tolerance. This study highlights the importance of taking multiple bacteria and their growth environment into account when understanding sanitizer response, as it varies in multispecies biofilm setups and according to nutrient availability.
Keywords: Listeria monocytogenes; Exopolysaccharide; Nutrient-deficient; Compact biofilm